OPTIMALISASI KEBIJAKAN PRIVASI DALAM MELINDUNGI HAK PRIVASI KONSUMEN PASCA-KEBOCORAN DATA PRIBADI (STUDI KASUS PT TOKOPEDIA) - Cynthia Kawai (2023)
Cases of consumer personal data leakage in Indonesia have repeatedly occurred, one of which is PT Tokopedia. This strengthens the importance of legal rules to protect consumer personal data, so that on September 20, 2022 Indonesia has officially passed Law Number 27 of 2022 concerning Personal Data Protection. The regulation on Personal Data Protection is a legal basis for protecting consumers and also as a reference or guideline for e commerce which is applied to the Privacy Policy. The purpose of this normative juridical research is to explain PT Tokopedia's Privacy Policy in improving consumer personal data protection after data leakage cases and whether the Privacy Policy has implemented the principles contained in Law Number 27 of 2022 concerning Personal Data Protection using a statute approach and case approach. Over time, Tokopedia's Privacy Policy has undergone changes or updates because it is part of compliance with laws and regulations and internal company policies, as well as one of Tokopedia's efforts to provide optimal protection of its users' personal data. Then, from the 8 (eight) principles of Law Number 27 of 2022 concerning Personal Data Protection, Tokopedia has not fulfilled the Principle of Responsibility because Tokopedia cannot guarantee 100% security of data provided or sent by users to Tokopedia on the grounds that the provision of information by users to Tokopedia is a risk borne by the users themselves.